Theater Arts as a Medium for Da'wah (Case Study of the Roda Theater Student Activity Unit, Al-Amien Prenduan University) - Renaldy Septyo Erick; Rosyidi Rosyidi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
Da'wah can be conveyed through various media, including theatrical arts that have visual and emotional appeal. The Teater Roda Student Activity Unit (UKM) at Al-Amien Prenduan University utilizes theatrical arts as a da'wah medium by integrating Islamic values in every performance. This study aims to examine the role of theatrical arts as a da'wah medium and identify the challenges faced by the Teater Roda Student Activity Unit. This study uses a qualitative approach with a case study method through observation, interviews, and documentation. The results show that theatrical arts play an effective role as a creative da'wah medium in conveying Islamic values, fostering religious awareness, shaping the mentality of preachers, and developing empathy and cooperation among members. However, its implementation faces various challenges, such as aligning members' visions, limited resources, competition with modern entertainment, and diverse audience responses. This study concludes that theatrical arts have great potential as a relevant and effective da'wah medium, provided it is suppomn rted by member development, creative innovation, and strengthening Islamic values in every activity.